2006
DOI: 10.2478/s11658-006-0018-2
|View full text |Cite
|
Sign up to set email alerts
|

The breakdown of bilayer lipid membranes by dendrimers

Abstract: Abstract:The BLM-system for studying the electrophysical properties of bilayer lipid membranes (BLM) was applied to investigate interactions between polyamidoamine (PAMAM) dendrimers and lipid bilayers. The cationic PAMAM G5 dendrimer effectively disrupted planar phosphatidylcholine membranes, while the hydroxyl PAMAM-OH G5 and carboxyl PAMAM G4.5 dendrimers had no significant effect on them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…The destabilization of the lipidic part of biological membranes has been investigated in several models of liposomes. Some dendrimers are able to remove lipids and create nanoholes in the structure of the lipid bilayer [39][40][41]. It has been shown that dendrimers change the properties of the lipid bilayer not only on the surface but also in the hydrophobic region [28,29,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The destabilization of the lipidic part of biological membranes has been investigated in several models of liposomes. Some dendrimers are able to remove lipids and create nanoholes in the structure of the lipid bilayer [39][40][41]. It has been shown that dendrimers change the properties of the lipid bilayer not only on the surface but also in the hydrophobic region [28,29,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…the rupture, were evaluated based on current-voltage characteristics using the relevant plots [9,10] (Fig. 1).…”
Section: Formation Of Planar Lipid Membranesmentioning
confidence: 99%
“…A customized multifunctional BLM-system, in which two chambers of a Teflon cell, each containing a platinized electrode, are separated by a septum with the orifice of 1.5 mm, was used to study the current-voltage (V-A) characteristics up to the picoampere level, as well as to monitor the kinetics of electric conductivity of planar BLMs [9,10]. The device allows measuring of the penetration of acid/alkaline ions (like SA or ASA) through a lipid bilayer, which is stabilized by the constant electric field of -30 /-20 mV.…”
Section: System For the Study Of Current-voltage Characteristics Of Pmentioning
confidence: 99%
See 2 more Smart Citations